A two-step chemical vapor deposition process for the growth of continuous vertical heterostructure WSe2/h-BN and its optical properties. Issue 28 (7th May 2021) - Alahmadi, M.; Mahvash, F.; Szkopek, T.; Siaj, M.
Abstract : Direct growth of WSe2 on hexagonal boron nitride via a two step CVD process. Abstract : The expansion of two-dimensional (2D) van der Waals heterostructure materials growth and synthesis leads to impressive results in the development and improvement of electronic and optoelectronic applications. Herein, a vertical WSe2 /hBN heterostructure was obtained via a dual CVD system, in which prior to the WSe2 growth a continuous monolayer hBN was obtained on a SiO2 /Si substrate. Comparing growth on SiO2 /Si and quartz substrates, we found that the underlayer of hBN leads to a desorption/diffusion process of tungsten (W) and selenium (Se) producing high-quality and large-area WSe2 growth. In contrast with WSe2 /SiO2 and WSe2 /quartz heterostructures, the photoluminescence properties of WSe2 /hBN exhibit a sharp intense WSe2 peak at 790 nm with a narrow full width at half-maximum (80 meV) due to no dangling bonds and dielectric effect of the hBN interface. The photoluminescence results suggest that the WSe2 /hBN heterostructure has high crystallinity with a defect-free interface.